Using Advanced Far-end Crosstalk Modeling Method for Simulations of Very High Speed Digital Lines - Jares, P.; Lafata, P. (Elektronika ir Elektrotechnika, 2012)
Digital subscriber lines are designed for efficient use in today's fixed access networks, which are made of symmetrical copper pairs. These lines allow to realize high-speed data transfers. The transmission performance of these connections is highly dependent on conditions of the real transmission environment. The main parameters affecting the transmission performance are the line attenuation and crosstalk noise. Considering that it is not possible to perform tests in real network access, because there were influencing data streams of end users, it is necessary to carry out all tests in the experimental access networks. Due to the cost of building such a experimental network, all the tests are carried out as simulations. For simulations it is necessary to accurately model the real conditions of transmission access network. The article describes methods for accurate modeling of the far end crosstalk, which is dominant for digital subscriber line. The second part of the article describes the crosstalk model used for calculating transmission performance of digital subscriber transmission line that uses vectored discrete multitone modulation to transfer user information. They are given specific values of the theoretical efficiency of transmission, depending on various conditions of transmission. Ill. 10, bibl. 8, tabl. 1 (in English; abstracts in English and Lithuanian).DOI: http://dx.doi.org/10.5755/j01.eee.121.5.1650